Ethnographic Communications of the Ngaben Ritual of Bali Hindus in Jakarta - Ketut PATERA; Mirza RONDA; Mikhael DUA (International Journal of Environmental, Sustainability, and Social Science, 2023)
Hindus believe that Ngaben facilitates and speeds up the process of liberating the soul of the sarira (smooth body) and the stula of the sarira (rough body). The Ngaben held in DKI Jakarta is different from Hindus in Bali. The aim of the research is to reveal the values contained in each pitra yadnya/Ngaben ceremony, especially for Hindus in North Jakarta. That its implementation is based on Vedic teachings, very flexible/adjustable to local conditions (Village, Kala, Patra). The Ngaben ceremony is a ritual that must be carried out even in overseas areas, according to local conditions and alignment of intent communications. The research was planned using a constructivist paradigm with a qualitative research methodology and an ethnographic research design of communication. In this approach, the researcher collects data and information through in-depth interviews and participatory observation from various sources who have knowledge and experience in implementing Ngaben in North Jakarta. The main focus is related to the use of verbal and non-verbal symbols used in the Ngaben ritual. The theoretical basis used by researchers is ritual communication and socio- cultural theory. The Ngaben ceremony held by the Banjar Hindu community in North Jakarta has a very high social aspect. The number of stages and series of ceremonies and the number of ceremonial equipment used to create social interaction in the ritual.